2022
DOI: 10.3389/fncel.2022.948454
|View full text |Cite
|
Sign up to set email alerts
|

The role of mechanobiology on the Schwann cell response: A tissue engineering perspective

Abstract: Schwann cells (SCs), the glial cells of the peripheral nervous system (PNS), do not only form myelin sheaths thereby insulating the electrical signal propagated by the axons, but also play an essential role in the regeneration of injured axons. SCs are inextricably connected with their extracellular environment and the mechanical stimuli that are received determine their response during development, myelination and injuries. To this end, the mechanobiological response of SCs is being actively researched, as it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…153 Hydrogels with a mechanical modulus lower than 1 kPa were not able to support effective growth and development of neural cells. 23 Indeed, SCs have been reported to express less adhesion proteins as the substrate stiffness decreases, 169 and to grow less processes when grown on soft substrates (<1 kPa). 23 Mechanical stretching is another property reported to influence cell behaviour.…”
Section: Reviewmentioning
confidence: 99%
“…153 Hydrogels with a mechanical modulus lower than 1 kPa were not able to support effective growth and development of neural cells. 23 Indeed, SCs have been reported to express less adhesion proteins as the substrate stiffness decreases, 169 and to grow less processes when grown on soft substrates (<1 kPa). 23 Mechanical stretching is another property reported to influence cell behaviour.…”
Section: Reviewmentioning
confidence: 99%
“…This task is frequently difficult, though, since natural cues are provided in complicated combinations within the intricate terrain of neural tissue. Thus, the surface modification of materials as platforms for studying cell viability, motility, differentiation, and apoptosis is the subject of extensive research [ 40 , 41 , 42 ].…”
Section: Importance Of Size Scale—topographymentioning
confidence: 99%
“…A puri ed AAVolig001-CBA-GFP was provided by Myrtelle (https://myrtellegtx.com), and AAV6-CBA-GFP was produced and puri ed in our laboratory by previously established methods. 20 Total four AAVs were used in the experiments, including 1) AAVolig001-CBA-GFP (AAVolig001-GFP, 1x10 13 GC/mL), 2) AAVolig001-PZ1shRNA-GFP (AAVolig001-PZ1shRNA, 1.2x10 13 GC/mL), 3) AAVolig001-scramble-GFP (AAVolig001-SC, 2x10 13 GC/mL), and 4) AAV6-CBA-GFP (AAV6-GFP, 2x10 13 GC/mL).…”
Section: Molecular Cloning and Aav Constructsmentioning
confidence: 99%
“…Recent studies found enriched Piezo1 (and Piezo2) expression in the SCs. 12 SCs have been shown to be required for mechanosensation, 13 suggesting that Piezo1 may participate in the mechanosensation of SCs. Using a classic Cre-Loxp strategy via a myelin protein zero (PMZ) promoter transcribing Cre for a conditional Piezo1 or 2 ablations in myelinating SCs (mSCs), a study shows that Piezo1 inhibits myelination while Piezo2 facilitates myelin formation in the PNS.…”
Section: Introductionmentioning
confidence: 99%